Pleiotropic Action of Selenium in the Prevention and Treatment of Cancer, and Related Diseases - Rustum, Youcef M. (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
This book will cover topics related to the preparation and use of heterogeneous catalytic systems for the transformation of renewable sources, as well as of materials deriving from agro-industrial wastes and by-products. At the same time, the ever-increasing importance of bioproducts, due to the acceptance and request of consumers, makes the upgrade of biomass into chemicals and materials not only an environmental issue, but also an economical advantage.